A community cross-sectional study on knowledge attitude and practice of prevention of COVID-19 among traditional tribal healers in the tribal subpopulation zone of Sirohi district of Rajasthan - Dwivedi, Rakhi; Dwivedi, Pradeep; S. Yadav, Suraj; Bohra, Gopal K.; Bhardwaj, Abhishek; Dutt, Naveen; Deora, Surender; Bhardwaj, Pankaj; Panda, Samhita; Singh, Pratibha; Gehlot, Sanjay; Singh, Kuldeep (International Journal Of Community Medicine And Public Health, 2022)
Background: Due to geographical location and limited health resources, tribal people in India still majorly consult traditional tribal healers of their community for their health needs. However, data regarding the knowledge, mode of practice, and utility of these tribal healers are not explored despite their significant role in the healthcare system. Our study assessed the levels of knowledge, attitude, and practices of traditional tribal healers toward the COVID-19 pandemic and its association with sociodemographic factors. Methods: Cross-sectional community based among the tribal healers of district Sirohi of Rajasthan. KAP study carried out with the help of a structured questionnaire about COVID-19, personal interviews, and community meetings among the tribal healers of district Sirohi of Rajasthan. A bivariate Pearson correlation analysis was performed, to identify factors related to knowledge, attitudes, and practices among socioeconomic data. Results: A total of 682 tribal healers participated in the study. Approximately, 55% of TH had a good knowledge score and 91% of TH had a good attitudinal score while 56% of TH had a good practice score. We observed that sociodemographic factors such as education status, education level, financial status in terms of income, marital status influenced the knowledge, attitude, and practices of tribal healers regarding COVID-19. Conclusions: With proper training, tribal healers can play the role of peer educators among the tribal population.